Integration of zero and sequential algorithm in shuffle exchange with Minus One Stage - Md Yunus, Nur Arzilawati; Othman, Mohamed; Mohd Hanapi, Zurina (Elsevier India, 2013)
This paper focused on comparing the algorithm based on shuffle exchange network connection to achieve the optimal routing time as well as the number of passes to route in a given permutation. The algorithms consist of six algorithms namely ZeroX, ZeroY, ZeroXbit, ZeroYbit, Sequential Increasing and Sequential Decreasing algorithm. These six algorithms will compare with the proposed Shuffle Exchange Network with Minus One Stage (SEN-). This paper also shows the details of the illustrative examples used to explain each algorithm. At the end of this chapter, the comparative analysis shows the performance of each algorithm with the integration of shuffle exchange connection pattern in terms of the execution time and number of passes.